A Low Frequency of IL-17-Producing CD8+ T-Cells Is Associated With Persistent Immune Activation in People Living With HIV Despite HAART-Induced Viral Suppression - Perdomo-Celis, Federico; Feria, Manuel G.; Taborda, Natalia A.; Rugeles, Maria T. (Frontiers in Immunology, 2018)
Immune activation is the hallmark of HIV infection, even in patients with highly active anti-retroviral therapy (HAART)-induced viral suppression. A major cause of immune activation during HIV infection is the intestinal microbial translocation as a consequence, among other factors, of the decrease and/or dysfunction of interleukin (IL)-17-producing T-cells, due to their role promoting the integrity of the intestinal barrier. A population of IL-17-producing CD8+ T-cells (Tc17 cells), characterized by the expression of CD161, has been described, but its relation with the persistent immune activation in non-viremic people living with HIV (PLWH) on HAART is unclear. By flow cytometry, we characterized the activation phenotype (evaluated by the expression of HLA-DR and CD38) of circulating CD161-expressing CD8+ T-cells; in addition, we explored the functionality of polyclonally-stimulated Tc17 cells in PLWH under HAART-induced viral suppression, and in healthy individuals. Finally, we determined the association of Tc17 cells with the expression of cellular and soluble activation markers. Circulating CD161-expressing CD8+ T-cells were decreased in PLWH compared with healthy individuals, despite their similar basal activation state. After polyclonal stimulation, IL-17 production was higher in CD8+ T-cells co-expressing HLA-DR and CD38 in healthy individuals. In contrast, although PLWH had a higher frequency of HLA-DR+ CD38+ CD8+ T-cells after stimulation, they had a lower production of IL-17. Interferon (IFN)-y-producing CD8+ T-cells (Tc1 cells) were increased in PLWH. The low Tc17 cells response was associated with a high expression of CD38 and programmed death 1 protein, high levels of soluble CD14 and the treatment duration. Finally, to explore potential immunomodulatory strategies, the in vitro effect of the anti-inflammatory agent sulfasalazine was assessed on Tc17 cells. Interestingly, a decreased inflammatory environment, death of activated CD8+ T-cells, and an increased frequency of Tc17 cells were observed with sulfasalazine treatment. Thus, our findings suggest that activated CD8+ T-cells have a marked capacity to produce IL-17 in healthy individuals, but not in PLWH, despite HAART. This dysfunction of Tc17 cells is associated with the persistent immune activation observed in these patients, and can be partially restored by anti-inflammatory agents.